PRAGMATICS ANALYSIS OF COMMIT EXPRESSION ACTED BY CHARACTERS IN “FRACTURED” MOVIE - Sihotang, Rintauli; Ambalegin, Ambalegin (Universitas Putera Batam, 2022)
This research analyzed the types of commissive act in a thrilled movie entitled “Fractured”. The data were commissive acts utterances in the movie. The data were observed by using observational and non-participatory technique. Therefore, the researchers watched the movie to get data. The researchers used pragmatics identity method and competence in equalizing to analyze the data. The researchers equalized the data with types of commissive acts theory proposed by Searle and Vanderveken (1985). The findings discovered 15 utterances showed commissive acts in the movie. Threaten had 1 data, accept had 2 data, promise had 6 data, refuse had 3 data, and offer had 3 data. The commissive acts of promise was found to be the most dominant type because all characters commonly promised to take action in the future to other characters in “Fractured” movie. Also, the type became the dominant because most of the speakers had the intention to do action that brought benefits for the hearers.